Odpowiedzi

Najlepsza Odpowiedź!
2010-02-09T17:32:30+01:00
E) - x - 3y = 5
y = - 2x

-x-3*(-2x)=5
-x+6x=5
5x=5
x=1

y=-2x=-2*1=-2

x=1
y=-2



f) 4x - y = 6
y = x

4x-x=6
3x=6
x=2
y=x=2

x=2
y=2


h) 2x- y = 4
x + y = 11
x=11-y

2(11-y)-y=4
22-2y-y=4
-3y=4-22
-3y=-18
y=6
x=11-6=5

x=5
y=6

i) x - 2y = - 3
2x + 3y = 8

x=-3+2y
2(-3+2y)+3y=8
-6+4y+3y=8
7y=8+6
7y=14
y=2
x=-3+2y=-3+4=1

x=1
y=2

p/s
z jednego równania wyliczasz niewiadomą x lub y i podstawiasz ją do drugiego równania

pozdrawiam:)





1 1 1
2010-02-09T17:33:54+01:00
E) - x - 3y = 5
y = - 2x

-x-3*(-2x)=5
y = - 2x

-x+6x=5
y=-2x

5x=5
y=-2x

x=1
y=-2x

x=1
y=-2

f) 4x - y = 6
y = x

4x-x=6
y=x

3x=6
y=x

x=2
y=2


h) 2x- y = 4
x + y = 11

x=11-y

2(11-y)-y=4
22-2y-y=4
-3y=4-22
-3y=-18
y=6
x=11-6=5

x=5
y=6






1 1 1